2017
DOI: 10.1515/macvetrev-2016-0095
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Staphylococcus Aureus Among Coagulase Positive Staphylococci from Animal Origin Based on Conventional and Molecular Methods

Abstract: The present study aimed to detect Staphylococcus aureus (S. aureus) among other coagulase positive staphylococci from animal origin by using conventional methods (biochemical tests and latex agglutination) and a molecular method, based on the nuc gene, as the gold standard and to assess the usefulness of these methods. For this purpose, total of 344 staphylococcal isolates were collected and analysed. A total of 156 isolates suspicious for S. aureus were detected by a conventional biochemical method -88 from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…They found that 100%, 92%, and 84% isolates were positive for catalase, coagulase, and heat-stable nuclease, respectively. The results of present study agreed with Another study done by Rusenova and Rusenov [10] that total of 156 isolates suspicious for S. aureus were detected by a conventional biochemical method. The majority of S. aureus strains gave typical biochemical reactions with the exception of 30 (19.2%) and 25 (16%) that were VP negative and weak positive in fermenting mannitol respectively.…”
Section: Detection Of 16srrna Meca and Pvl Genes By Polymerase Chainsupporting
confidence: 92%
See 1 more Smart Citation
“…They found that 100%, 92%, and 84% isolates were positive for catalase, coagulase, and heat-stable nuclease, respectively. The results of present study agreed with Another study done by Rusenova and Rusenov [10] that total of 156 isolates suspicious for S. aureus were detected by a conventional biochemical method. The majority of S. aureus strains gave typical biochemical reactions with the exception of 30 (19.2%) and 25 (16%) that were VP negative and weak positive in fermenting mannitol respectively.…”
Section: Detection Of 16srrna Meca and Pvl Genes By Polymerase Chainsupporting
confidence: 92%
“…Such strains have been correlated to life-threatening infections and deaths, predominantly severe skin infections as well as tissue necrosis. Additionally, Rusenova and Rusenov [10] demonstrated that pvl exotoxin kills leukocytes (neutrophils and macrophages) in different mammals (viz. rabbits, cattle, and humans).…”
Section: Detection Of 16srrna Meca and Pvl Genes By Polymerase Chainmentioning
confidence: 99%
“…These findings were supported our following results, the positivity of Voges-Proskauer were recorded in 18 isolates from raw milk samples and 8 isolates from local pasteurized milk samples (Table2). Higher results were illustrated by Rusenova and Rusenov (2017) who found that 73% of coagulase positive Staphylococcal strains isolated from different animals were Voges-Proskauer positive. This variation may back to level of contamination, number of samples and method of isolation (Fagundes and Oliveira, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Цей процес може спростити використання тест-систем, наприклад . Проте різні родини стафілококів можуть мати мінливі або однакові біохімічні ознаки, що унеможливлює повну їх ідентифікацію мікробіологічними методами [8]. MALDI-ToF MS сучасний метод, який пропонують використовувати як новий золотий стандарт, однак його застосування також потребує виділення чистої культури [9,10].…”
Section: мікробіологія епізоотологія та інфекційні хворобиunclassified